2013
DOI: 10.1111/jam.12403
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of dibenzofuran via multiple dioxygenation by a newly isolated Agrobacterium sp. PH-08

Abstract: Aims: To demonstrate the biodegradation of dibenzofuran (DF) and its structural analogs by a newly isolated Agrobacterium sp. PH-08. Methods and Results: To assess the biodegradation potential of newly isolated Agrobacterium sp. PH-08, various substrates were evaluated as sole carbon sources in growth and biotransformation experiments. ESI LC-MS/MS analysis revealed the presence of angular degrading by-products as well as lateral dioxygenation metabolites in the upper pathway. The metabolites in the lower path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…It has also been reported that Agrobacterium strains can carry a symbiotic plasmid (Sym) and form nodules in legumes [5–7]. In addition, several reports of Agrobacterium are about their roles as human pathogens maintaining relationships with nosocomial infections [8], and as a biotechnological tool [9], for example, in programs for obtaining genetically modified plants [10].…”
Section: Full-textmentioning
confidence: 99%
“…It has also been reported that Agrobacterium strains can carry a symbiotic plasmid (Sym) and form nodules in legumes [5–7]. In addition, several reports of Agrobacterium are about their roles as human pathogens maintaining relationships with nosocomial infections [8], and as a biotechnological tool [9], for example, in programs for obtaining genetically modified plants [10].…”
Section: Full-textmentioning
confidence: 99%
“…The dioxygenases have a wide range of substrates specificity and belong to the Rieske non-heme iron oxygenases. A few reports have implicated bacteria in the degradation of DF through both dioxygenation pathways Le et al 2014).…”
Section: Aerobic Bacterial Degradation Of Dioxinsmentioning
confidence: 99%
“…Agrobacterium sp. PH-08 isolated from a saw mill waste dump site also degraded DF through both angular and lateral dioxygenation (Le et al 2014). Growth of the organism was also sustainable on biphenyl but not as efficient as when DF was used as carbon.…”
Section: Aerobic Degradation Of Dioxins By Other Bacterial Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other microorganisms can conduct co-metabolic degradation of DBF via lateral dioxygenation when cultivated with biphenyl (BP) or naphthalene (Becher et al 2000;Kaiya et al 2012;Li et al 2009;Shi et al 2014;Stope et al 2002). A few studies have shown that several bacteria can degrade DBF via both pathways (Jaiswal et al 2011;Le et al 2014;Yamazoe et al 2004). Bacteria using the angular dioxygenation pathway can easily degrade DBF channeled into the tricarboxylic acid (TCA) cycle ; Additional file 1: Figure S1), while bacteria co-metabolizing DBF via lateral (1) 4-Hydroxy-3-methyl-6-phenylbenzofuran-2-carboxylic acid ethyl ester showed selective and potent cytotoxicity against tumors (Hayakawa et al 2004a, b).…”
Section: Introductionmentioning
confidence: 99%